(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
The dinosaur record from Iran includes footprints from the Liassic Ab-e-Haji Formation of Neizar Valley (Kerman Province, central-eastern Iran), a single footprint from the Javaherdeh Formation near Zerab (Alborz Mounts, NE Iran), and skeletal remains from the Late Jurassic-earliest Cretaceous Ravar Formation of the Ab Bid Syncline (Kerman Province). Contrary to previous identifications, no footprints from the Neizar Valley belong to ornithopods; they can all be referred to theropod trackmakers. The Zerab footprint, on which the ichnospecies Iranosauripus zerabensis is based, is an undiagnostic theropod footprint and probably was lost. The skeletal remains are represented by bone fragments and a tooth of a mid-sized theropod, which represent the first dinosaur osteological record in this part of the Middle East. The Ab Bid Syncline has a high potential for further future discoveries.